2012
DOI: 10.1111/j.1365-3016.2012.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventions with Vitamins B6, B12 and C in Pregnancy

Abstract: The water‐soluble vitamins B6, B12 and C play important roles in maternal health as well as fetal development and physiology during gestation. This systematic review evaluates the risks and benefits of interventions with vitamins B6, B12 and C during pregnancy on maternal, neonatal and child health and nutrition outcomes. Relevant publications were identified by searching PubMed, Popline and Web of Science databases. Meta‐analyses were conducted for outcomes where results from at least three controlled trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
70
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 110 publications
3
70
0
3
Order By: Relevance
“…Individuals with a low intake of meat and dairy products, such as vegans and vegetarians, are at high risk of vitamin B-12 deficiency (5). Several studies conducted in low-and middleincome countries also have reported a high prevalence of vitamin B-12 deficiency, particularly in pregnant women and young children (6), in part due to inadequate dietary vitamin B-12 intake (7,8), increased requirements during pregnancy and lactation, and low vitamin B-12 content and bioavailability in breast milk (9). Micronutrient supplementation is a common strategy to prevent and treat cobalamin deficiency (10), and there is emerging interest in mandatory food fortification with vitamin B-12 (11).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with a low intake of meat and dairy products, such as vegans and vegetarians, are at high risk of vitamin B-12 deficiency (5). Several studies conducted in low-and middleincome countries also have reported a high prevalence of vitamin B-12 deficiency, particularly in pregnant women and young children (6), in part due to inadequate dietary vitamin B-12 intake (7,8), increased requirements during pregnancy and lactation, and low vitamin B-12 content and bioavailability in breast milk (9). Micronutrient supplementation is a common strategy to prevent and treat cobalamin deficiency (10), and there is emerging interest in mandatory food fortification with vitamin B-12 (11).…”
Section: Introductionmentioning
confidence: 99%
“…1). Una alimentación deficiente en micronutrientes está relacionada con preeclampsia, partos prematuros, crecimiento intrauterino retardado (CIR), bajo peso al nacer (BPN) y malformaciones congénitas (1,2).…”
Section: Introductionunclassified
“…The well-nourished human adult has about 2-5 mg of the vitamin, the majority being stored in the liver which is adequate without repletion for 3-5 years. A healthy prepregnancy body stores of B12 are, therefore, sufficient to meet increased demand during pregnancy [13].…”
Section: Vitamin B12 Homeostasis and Requirements During Pregnancy Anmentioning
confidence: 99%